Modulation of Cytokine-Induced Astrocytic Endothelin-1 Production as a Possible New Approach to the Treatment of Multiple Sclerosis - Hostenbach, Stéphanie; D’Haeseleer, Miguel; Kooijman, Ron; De Keyser, Jacques (Frontiers in Pharmacology, 2020)
Background: In the human central nervous system (CN), resting astrocytes do not visually show endothelin-1 (ET-1)-like immunoreactivity. In patients with multiple sclerosis (MS), an inflammatory disorder of the CNS, high levels of ET-1 are found in reactive astrocytes in demyelinated plaques. ET-1 may contribute to the pathology of MS by interrupting the blood-brain-barrier, enhancing inflammatory responses, excitotoxicity and reducing cerebral blood flow. Methods: We used the human astrocytoma cell line 1321N1 to investigate the role of inflammatory cytokines involved in MS lesions (IL-1β, TNF-α, IFN-γ, LPS, IL-10, TGF-β) on astrocytic ET-1 upregulation. Prucalopride, rolipram, fenofibrate, fluoxetine, simvastatin, daglutril, and resveratrol were investigated as potential candidate drugs to suppress cytokine-induced astrocytic ET-1 production. Effects on ET-1 production were measured using both ELISA and RT-qPCR. Results and Conclusions: ET-1 secretion by astrocytoma cells was only stimulated by the pro-inflammatory cytokines IL-1β and TNF-α. Fluoxetine, simvastatin, and resveratrol significantly inhibited this IL-1β- and TNF-α-induced ET-1 production. Simvastatin and resveratrol significantly reduced ET-1 mRNA levels, indicating an effect at the level of transcription. Fluoxetine significantly reduced endothelin converting enzyme-1 mRNA levels, suggesting and effect at the level of protein-processing. The required concentrations of simvastatin (>0.1 µM) and resveratrol (>10 µM) cannot be achieved in humans using pharmacologically accepted doses. Fluoxetine exerted a significant inhibitory effect on ET-1 secretion at a concentration of 5 µM, which is pharmacologically achievable in human brain, but the effect was modest (<50% suppression) and probably not sufficient to obtain a clinically relevant ET-1 effect. Our in vitro model can be a useful screening tool in the development of new drugs to suppress astrocytic ET-1 production. The effect of simvastatin was for the most part mediated via the mevalonate pathway, suggesting that this might be an interesting target for further drug development.